Uma proposta metodológica para a estimaç\~ao da matriz de absorç\~ao de investimentos para o período 2000-2009 - Thiago Miguez; Fabio Freitas; Gabriel Coelho Squeff; Lucas Ferraz Vasconcelos; Thiago Moraes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper presents an estimation of investment flows for Brazil between 2000 and 2009 at the sectoral level through Capital Flow Tables (CFTs). CFTs were estimated for the economy as a whole and according the origin of products (domestic or imported). We use data from MDIC, IBGE, BNDES, Petrobras, and we adopt Brazilian National Accounts classification. Among others, CFTs can be used to elaborate multisectoral dynamic models and to calculate capital stock and multifactor productivity at the sectoral level.
Keywords: C82; E22; 330; capital flow table; gross fixed capital formation; national accounts